2020
DOI: 10.4081/ija.2020.1581
|View full text |Cite
|
Sign up to set email alerts
|

Integrated application of biochar and bio-fertilizer improves yield and yield components of Cowpea under water-deficient stress

Abstract: A low amount of organic matter and insufficient irrigation are two main challenges facing successful crop production in arid and semiarid regions. Application of biochar as an organic amendment to soil not only can help increase organic matter in soil, but also may alleviate adverse effects of water deficit on plant growth and yield production. To test this hypothesis, a two-year field experiment was conducted to assess the effect of sugarcane biochar on yield and yield components of cowpea in water-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In a field study, Grabi ński and Wyzi ńka [53] concluded that the addition of superabsorbent polymers at the rate of 30 kg/h in winter wheat elevated all the growth and yield parameters in water stress conditions, which strongly endorsed our experimental treatment of the KPAM polymer and the results. Similarly, Moosavi et al [54] showed that the cultivation of cowpea with biochar enhanced the seed number per plant due to the relief of water-deficient stress and a higher phosphate and potassium content. Other studies also endorsed that biochar and nitrogen fertilizer improved the yield-related characteristics in arid climates [55,56].…”
Section: Discussionmentioning
confidence: 95%
“…In a field study, Grabi ński and Wyzi ńka [53] concluded that the addition of superabsorbent polymers at the rate of 30 kg/h in winter wheat elevated all the growth and yield parameters in water stress conditions, which strongly endorsed our experimental treatment of the KPAM polymer and the results. Similarly, Moosavi et al [54] showed that the cultivation of cowpea with biochar enhanced the seed number per plant due to the relief of water-deficient stress and a higher phosphate and potassium content. Other studies also endorsed that biochar and nitrogen fertilizer improved the yield-related characteristics in arid climates [55,56].…”
Section: Discussionmentioning
confidence: 95%
“…In most cases, biochar application improved the properties of the soil, although in some cases, its adverse effects were observed, which may be due to the insufficient application of biochar. The beneficial effects of biochar increase the availability of water (Cornelissen et al, 2013;Moosavi et al, 2020), thereby increasing soil moisture retention (Buss et al, 2012) and improving soil chemical properties such as increasing the level of soil organic carbon, soil nitrogen and nutrient uptake (Ma et al, 2016). There was no correlation between the root characteristics, SR and DMY (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] On the other hand, in the spreading method used by farmers, seeds are spread on the smoothed soil surface, followed by narrow cultivation. In Pakistan, wheat grain yield per hectare is still 65−70% lesser than that in other wheat-producing countries 3,8,9 even though farmers use excessive amounts of irrigation 10,11 and fertilizers to boost crop yield in flat sowing method.…”
Section: Introductionmentioning
confidence: 98%